PELAYANAN PUBLIK PADA PUSAT KESEHATAN MASYARAKAT (PUSKESMAS) BERANGAS KECAMATAN ALALAK KABUPATEN BARITO KUALA - Muhammad Jamili (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
The development of population and settlements in this region since 2 decades ago demands to be fulfilled by other aspects, especially the basic needs of the community such as aspects of education, health, social and religious facilities. The influence of the construction of road infrastructure including the development of population and settlements, and this all impacts on the demands for the availability of public facilities such as public health facilities. Starting from this all research needs to be done whether public health services have followed the progress of the community itself. The purpose of this study was to determine the public services provided by Puskesmas to community members. The research method used is a descriptive method with a qualitative approach that is describing or describing the state of the Berangas Community Health Center in Alalak District. The results showed that the Berangas Health Center in providing health services to the general population could be said to be quite good. However, there are some complaints from the public regarding public services at the Berangas Health Center, among others, the services are considered to be slow, and this is caused by the lack of discipline of the staff in the determination of service hours listed at the Puskesmas. community members.